2017
DOI: 10.1021/acsami.7b08807
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive, Uniform, and Reproducible Surface-Enhanced Raman Spectroscopy Substrate with Nanometer-Scale Quasi-periodic Nanostructures

Abstract: We introduce a simple and cost-effective approach for fabrication of effective surface-enhanced Raman spectroscopy (SERS) substrates. It is shown that the as-fabricated substrates show excellent SERS effects in various probe molecules with high sensitivity, that is, picomolar level detection, and also good reliability. With a SERS enhancement factor beyond 10 and excellent reproducibility (deviation less than 5%) of signal intensity, the fabrication of the SERS substrate is realized on a four-inch wafer and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Further detailed experiments are needed to highlight the contribution of periodicity on the SERS enhancements. The existing literature has demonstrated that the periodic structures‐based sensors achieved from various chemical approaches acted as efficient SERS platforms regarding sensitivity, selectivity, and signal uniformity . Herein, Au‐coated ripple structures have shown the superior EFs to some of earlier published results, and the fabricated methodology in the present study is simple, viable, and could be cost‐effective when compared with the chemical approaches.…”
Section: Resultsmentioning
confidence: 53%
“…Further detailed experiments are needed to highlight the contribution of periodicity on the SERS enhancements. The existing literature has demonstrated that the periodic structures‐based sensors achieved from various chemical approaches acted as efficient SERS platforms regarding sensitivity, selectivity, and signal uniformity . Herein, Au‐coated ripple structures have shown the superior EFs to some of earlier published results, and the fabricated methodology in the present study is simple, viable, and could be cost‐effective when compared with the chemical approaches.…”
Section: Resultsmentioning
confidence: 53%
“…All measured spectra were repeatable with minimum variation in intensity and relative standard deviation (RSD) was found to be ~1.5%. To the best of our knowledge, this is the highest reproducibility in SERS sensing, where signal variations between 5% and 10% are common among the best ever conventional substrates . Detection of biochemicals in the form of liquid and gas (specifically volatile organic compounds) has great relevance in biomedical, chemical, homeland security and environmental monitoring applications and demands very high sensitivity to meet the practically relevant end use applications.…”
Section: Resultsmentioning
confidence: 99%
“…One of the biggest challenges is uniform distribution of hot spots throughout the array of nanostructures for reproducible SERS spectra. [57,[64][65][66] Moreover, although SERS nanostructures are usually arranged in two dimensions, a different design of plasmonic nanostructures should be developed to incorporate more hot spots on a given substrate area.…”
Section: Introductionmentioning
confidence: 99%